Proceedings of the International Conference on Sustainable Development of Cross-Border Regions: Economic, Social and Security C 2019
DOI: 10.2991/icsdcbr-19.2019.172
|View full text |Cite
|
Sign up to set email alerts
|

Time perspective of a women with cancer: research results from a border region

Abstract: In contemporary society, with the increasing number of people with cancer, the problem of increasing interest in cancer diseases of female reproductive organs is particularly acute. This is associated with a significant rejuvenation of the contingent of patients suffering from malignant neoplasms of the gynecological system and the breast. An empirical study has revealed that the inability to control one's life in a disease can lead to the loss of a person's temporal perspective, meaning of life, deformation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…This study concerned the relationship between different dimensions of time in cancer patients. None of the previous quantitative studies tracked the influence of either time of treatment or the rhythm of chemotherapy on temporal perspectives as defined by the ZTPI ( Nozari, Janbabai & Dousti, 2013 ; Kroyan, Gurova & Ippolitova, 2019 ; Furmańska et al, 2019 ). Overall, the study found that linear time and the rhythm of chemotherapy are less important than hypothesized in terms of their impact on temporal perspectives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study concerned the relationship between different dimensions of time in cancer patients. None of the previous quantitative studies tracked the influence of either time of treatment or the rhythm of chemotherapy on temporal perspectives as defined by the ZTPI ( Nozari, Janbabai & Dousti, 2013 ; Kroyan, Gurova & Ippolitova, 2019 ; Furmańska et al, 2019 ). Overall, the study found that linear time and the rhythm of chemotherapy are less important than hypothesized in terms of their impact on temporal perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this cancer patients’ sample mean level of present hedonism is low (3.08) compared with other studies. Research performed in Iran ( Nozari, Janbabai & Dousti, 2013 ) on 87 breast and digestive system cancer patients revealed present hedonism to be comparable (3.06), but a study from Russia on 50 reproductive system cancer patients found notably higher levels of hedonism (3.46) ( Kroyan, Gurova & Ippolitova, 2019 ), and another Polish study of 150 patients of various cancers a much higher one (3.60) ( Furmańska et al, 2019 ). However, none of the abovementioned studies included information about whether patients were in chemotherapy, which is likely the reason for the current sample’s lowered scores on present hedonism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation